INHIBITION OF GASTRIC DEGRADATION OF OMEPRAZOLE USING A pH-SENSITIVE POLYMER AS A BINDER IN TABLET FORMULATION - OLORUNSOLA, EMMANUEL O.; E. UDOH, IMO; MAJEKODUNMI, STEPHEN O.; ODIONG, INIOBONG J.; EBONG, UWAKMFON O. (International Journal of Applied Pharmaceutics, 2021)
Objective: This work was aimed at formulating omeprazole tablets using afzelia gum as a binder that is capable of inhibiting the gastric degradation of the drug. Methods: Afzelia gum at different concentrations of 0, 5, 10, 15, 20 and 30% was used as a binder to formulate omeprazole tablets. The tablets were formulated by direct compression and the batches labelled F1 to F6 respectively. A batch containing 15% hydroxypropyl methylcellulose (F7) was also formulated. The tablets were characterized; and dissolution in a pH 1.2 dissolution medium over 120 min period was studied. Aliquots taken every 20 min were analyzed by ultraviolet spectrophotometry to determine the amount of drug released and not degraded. Results: Amounts of drug released and not degraded at time 120 min were 53.1%, 57.3%, 57.8%, 58.8%, 62.1%, 83.4% and 90.0% for F1 to F7 respectively. Conclusion: Afzelia gum at a concentration of 30% is suitable for use as a binder in tablet formulation of omeprazole to ensure substantial inhibition of gastric degradation of the drug.